2010
DOI: 10.1039/c0cc00709a
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of carbon nanotubes by photo- and thermal-responsive polymers containing azobenzene unit in the backbone

Abstract: Photo- and thermal-responsive polymers containing azobenzene units in the main chain have been utilized as removable dispersants for single-walled carbon nanotubes (SWNTs) in organic solvents. Intermolecular interactions between SWNTs and the polymers are reversibly controllable by tuning the trans-cis composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…To the best of our knowledge, only three pioneering studies on the photochemical dispersibility control of SWNTs using photoresponsive polymers have recently been reported. One is the photocleaving of poly(ethyleneglycol)‐terminate malachite green,7 while other examples are based on change in cavity spaces due to the photoisomerization of the backbone of π ‐conjugated polymers 8, 9. However, non‐polymeric dispersants with a photoresponsibility in an aqueous phase have not yet been developed.…”
Section: Observed D and The Corresponding Uncertainties (In Bracket) mentioning
confidence: 99%
“…To the best of our knowledge, only three pioneering studies on the photochemical dispersibility control of SWNTs using photoresponsive polymers have recently been reported. One is the photocleaving of poly(ethyleneglycol)‐terminate malachite green,7 while other examples are based on change in cavity spaces due to the photoisomerization of the backbone of π ‐conjugated polymers 8, 9. However, non‐polymeric dispersants with a photoresponsibility in an aqueous phase have not yet been developed.…”
Section: Observed D and The Corresponding Uncertainties (In Bracket) mentioning
confidence: 99%
“…Among these polymer materials, polyazobenzene has unique physical and chemical light-induced interconversion properties that make them ideal photo-triggered switches for drug delivery systems. An example of this is shown in the study done by Umeyama et al 48 involving polyazobenzene polymers used as dispersants for the single-walled carbon nanotubes. These nanotubes were highly tunable through intermolecular interactions within the polymer, thereby demonstrating the possibility of carbon nanotube-based polymeric drug delivery systems for therapeutic purposes.…”
Section: Commonly Used Nanomaterials For Photo-triggered Medical Applmentioning
confidence: 99%
“…Wang et al reported the synthesis of polyimides containing azobenzene unit as the cross linker [15]. In 2010 a study showed that azobenzene containing polymers can be used as the dispersing agents for carbon nanotubes [16]. Several conjugated polymers having azobenzene unit on the backbone were reported for interesting applications such as nonlinear optical devices, self structuring polymer films and photoresponsive polymers [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%